A prospective study on the transition in frailty state and its predictors in community-based older adults in India - Amruta Kulkarni; Aarti Nagarkar (Clinical Epidemiology and Global Health)
Background: Frailty is a complex concept, and individuals' frailty status can change over time. Understanding these transitions is crucial for preventive interventions and healthcare management. This study investigates the factors influencing the transitions between non-frail, pre-frail, and frailty in a cohort of older adults in India. Methods: A cohort of 317 men and women aged 60 years and older was followed for an average of 16 months. Frailty was measured using the Fried phenotype. Multinomial regression analysis assessed the associations of sociodemographic, lifestyle, functional health, social, and other variables with frailty transitions (worsening, improvement, and retention in the same state). Results: The mean age on enrolment was 70.4 years, and 56 % were females. Over the period, 30.6 % and 1.5 % of robust worsened to pre-frail and frail category, respectively; 12 % of pre-frail worsened to a frail category and 16 % of frail experienced death or medical complications. Slum residence, baseline impairment of ADL, and balance predicted robust worsening. Tobacco or alcohol use, difficulty in IADL, and balance impairment (Adjusted Relative Risk ratio [ARR]:3.05 CI:1.05–8.86) predicted pre-frail worsening. Literacy (ARR:3.21 CI:1.02–10.11) and social networks (ARR:1.10 CI:1.03–1.16) predicted pre-frail improvement. Cognition and ADL scores were associated with transitions between robustness and pre-frailty in both directions. Conclusion: Identifying factors such as impaired balance, functional difficulties, literacy, social networks, and cognitive abilities as potential predictors of frailty transition presents a promising outlook for frailty management in older adults.